Understanding past, present, and future climate changes from East to West Africa - Gebrekirstos, Aster; Bräuning, A.; Noordwijk, Meine van; Mitlöhner, Ralph (2011)
Tree rings and stable isotopes in tree rings provide evidence of past climate variability. Given the short instrumental climate records that exist in Africa, dendrochronology adds an essential longer-term perspective on climate change and variability and on the adaptation of agroforestry landscapes and forest ecosystems. Tree-ring analyses were conducted as part of three independently established international research collaborations with different partner institutes in Germany and Africa. Stable carbon and oxygen isotopes in tree rings of Sclerocarya birrea from the Sahel region (Burkina Faso) showed strong climatic signals. Tree-ring chronologies spanning more than 100 years are under development for Burkina Faso and Tanzania. The ongoing project in Munessa Forest, Ethiopia may result in chronologies of more than 350 years. Finally, the tree- ring series developed in the three projects will be combined to establish large-scale correlation patterns between tree growth and sea-surface temperatures in order to explore continent-wide climate teleconnections. In order to have representative data sets and draw continent-wide recommendations, however, there is a need to extend the study to other parts of Africa.